ANALYSIS OF CAPITAL ADEQUACY RATIO EFFECT, NON PERFORMING LOAN, OPERATIONAL LOAD OPERATIONAL INCOME AND LOAN TO DEPOSIT RATIO OF PROFIT CHANGES WITH CREDIT DISTRIBUTION AS AN INTERVENING VARIABLE - Ervina, Ervina (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study is to analyze the effect of Capital Aduquacy Ratio (CAR), Non Performing Loans (NPL), Operating Costs on Operating Income (OCOI) and Loan Deposit Ratio (LDR) on Changes in Profit and its influence mediated by Credit Distribution. The object of this research is banking companies listed on the Indonesia Stock Exchange (IDX) for the 2007-2017 period. The sampling technique uses a purposive sampling method with a sample of 14 selected banks in order to obtain 154 observational data. Data analysis method is secondary data using Smart PLS (Partial Least Square). The results indicated that CAR and LDR did not have a significant positive effect on earnings changes. NPL has a negative effect, but not significantly to changes in earnings. The OCOI variable has a significant negative effect on changes in earnings. OCOI and LDR ratios have a significant effect on changes in earnings through lending. The CAR and NPL variables have no significant effect on changes in earnings through lending.